Duodenal duplication cyst in an adult: a rare case. - Raghunath P,; Neha K,; Sakshi S,; Rajgopal S,; Kuladeepa AV, (Department of Surgery, UKM Medical Centre, 2014)
Duodenal duplication cysts are rare congenital anomalies, found commonly in infants and children. In rare instances they can occur in adults, often manifesting clinically as pancreatitis. We here present one such case of an 18-year-old female, who presented with symptoms of duodenal obstruction, weight loss and pancreatitis. She was diagnosed as having a duodenal duplication cyst (DDC) on a CT scan. She made a good recovery after a total cyst excision. This case report aims to highlight the importance of clinicians having duplication cysts in their list of differential diagnoses as these cases are often under-diagnosed due to their rare occurrences.